2013
DOI: 10.2118/159801-pa
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Dependent Natural-Fracture Permeability in Shale and Its Effect on Shale-Gas Well Production

Abstract: This paper presents an investigation of the effect of pressuredependent natural-fracture permeability on production from shale-gas wells. The motivation of the study is to provide data for the discussion of whether it is crucial to pump proppant into natural fractures in shale plays. Experiments have been conducted on Bakken-shale core samples to select appropriate correlations to represent fracture conductivity as a function of pressure (the actual characterization of fracture conductivity under stress for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(75 citation statements)
references
References 29 publications
2
73
0
Order By: Relevance
“…Cho et al [7] conducted an experimental study to investigate the relationship between the natural fracture permeability and reservoir pressure using Bakken core samples. Zhang et al [19] demonstrated that high proppant concentration was critical to the maintenance of effective fracture conductivity.…”
Section: Stress-dependent Fracture Permeability and Contact Surface Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Cho et al [7] conducted an experimental study to investigate the relationship between the natural fracture permeability and reservoir pressure using Bakken core samples. Zhang et al [19] demonstrated that high proppant concentration was critical to the maintenance of effective fracture conductivity.…”
Section: Stress-dependent Fracture Permeability and Contact Surface Areamentioning
confidence: 99%
“…The influence of the natural fractures will be presented in a separate work. The compliance of hydraulic fractures spans a wide range according to the literature due to the variations in proppant embedment and rock properties [6,7]. In the work by Suarez-Rivera and Burghardt [6], the authors reported the measured fracture compliance of approximately 0.11 MPa −1 for propped fractures and 0.34 MPa −1 for unpropped fractures.…”
Section: Stress-dependent Fracture Permeability and Contact Surface Areamentioning
confidence: 99%
See 1 more Smart Citation
“…First, we simulate an ideal case in which fracture network conductivity doesn't change with time. In a second, more realistic case, the expected reduction in permeability (pressuredependent permeability, PDP) of the simulated fracture network caused by the increasing effective stress during production is simulated as (Cho et al, 2013;Raghavan et al, 2004):…”
Section: Impact Of Natural Fracturesmentioning
confidence: 99%
“…SG has complex characteristics such as large reserves, long production cycle, somewhat expensive exploration costs compared with other unconventional types of gas reservoirs and so on. The complexity of SG brings that the fields of SGR during the past years are diverse, which include theoretical SGR of analyzing the foundation of SG exploration [1,2,10,[24][25][26], model investigation in SG [24,[27][28][29][30][31][32][33], technical and economic research of considering the potential application of SG [7,25,[33][34][35][36], the environmental impact assessment in SG exploitation [21,[37][38][39][40][41][42][43][44][45][46][47][48] and many others. Anyway, with the evolution from initial exploitation to the more and more complicated development of SG, the diverse research of SG can be found in available literature during past decades.…”
Section: Introductionmentioning
confidence: 99%